Validation and implementation of an intraoperative parathyroid hormone assay and workflow: practical advice for endocrine surgery centres - Staibano Phillip; Ahmed Basma; Ivica Josko; Macri Joseph; Au Michael; Zhang Han; Pasternak Jesse D.; Bhandari Mohit; Kavsak Peter (Journal of Laboratory Medicine)
Intraoperative PTH (IOPTH) can be challenging to offer through central laboratories despite its clinical benefit. We describe the implementation of a central laboratory-based IOPTH assay and workflow in a tertiary care centre.